An Assessment of Parents-Adolescents Communication on Sexual and Reproductive Health Matters between Evelyn Hone College Lecturers and their Adolescent Children, Lusaka, Zambia - Haakonde, Titus; Chisumbe, Sampa; Chibwe, Mary; Iwol, Kennedy (Edelweiss Applied Science and Technology, 2018)
Background: One of the neglected issues in our society today, is effective communication between parents and adolescents on matters of Sex and Reproductive Health. This problem has saliently exposed the adolescents to the risk of contracting Sexually Transmitted Infections (STIs) and teenage pregnancies as well as engaging in drug and substance abuse. As such, this study aimed at assessing the extent of parent-adolescents communication on Sexual and Reproductive Health (SRH) matters among the Lecturers at Evelyn Hone College and their children. Methods: A cross-sectional descriptive survey study design was used in which 85 respondents were conveniently recruited into the study. Data collection was through pre-tested semi structured questionnaires. Analysis of data was done using SPSS version18 and graphs were generated using Microsoft Excel. Results: The study revealed that parents were not very much willing to offer SRH education to their adolescent children. They preferred having their children being taught SRH education by non-family members rather than themselves. Additionally, it was further shown that parents were initiators of SRH discussions in a home and not children. Further, it was also revealed that adolescents who had ever received SRH education from their parents were less likely to be promiscuous as compared to those who lacked such education. It was however noted that most female lecturers spent much of their time educating their children in SRH than their male counterparts. Conclusion: The findings suggested that parenthood and gender play key roles in the communication of SRH matters between parents and adolescent children. As it was seen that female Lecturers spent much time communicating with their adolescent children on SRH issues than the male Lecturers. However, there is need to create avenues other than a home where adolescents will be able to openly discuss a nd share experiences about SRH especially with the guidance of a parent.